Nursing care of a child hospitalized in the opinions of parents - Gawlik, Katarzyna; Waksmańska, Wioletta; Łukasik, Renata (Nursing in the 21st Century, 2012)
NURSING CARE OF A CHILD HOSPITALIZED IN THE OPINIONS OF PARENTSIntroduction. Child who is helpless and the dependent person, affected by the disease, pain, suffering, requires care and concern for the nursing staff. Nurse cared for the child in the ward should be characterized by specific predispositions in order to meet the demands posed.Aim.The aim of this study was to investigate the opinions of parents on satisfaction with nursing care for the child in the ward and parents expectations about the behavior of staff towards the sick children.Material and methods. The study was conducted from January to May 2011 in the Pediatrics Hospital in the city of Bielsko-Biała, in a group of 101 parents. Filled a anonymous survey.Results. The analysis of the collected data show that the respondents are satisfied with the nursing care of their children. Parents met with friendliness and openness, to a lesser degree of negative traits, including haste or reluctance. Behavior of the nurses to the sick children depend on the personality of nurses, income and working conditions.Conclusions. Parents expect the nurse competence, kindness and good verbal communication. Nurses in the care of the child should avoid negative behaviors, particular hurry.